Morpho-physiological responses of cowpea to different time and rates of compost application under water stress (2017)
Drought and poor soil fertility constitute serious threats to crop production. Water stress reduces crop yield by about 80%. In this study, the effect of Mexican sunflower compost on the morpho-physiological and biochemical responses of cowpea under water stress (100, 50 and 25% field capacity) was investigated. Compost was applied at different rates (10:C1 and 15 t/ha: C2) and at different times (two weeks before (B) and after (A) planting of cowpea seeds as well as repeated application (BA) during one cropping season. Data were collected on growth and yield parameters, chlorophyll and carotenoid content and stomata density. The results showed that although water stress adversely affected cowpea growth and development, soil amendment with compost increased the growth and yield parameters of cowpea. Variations were however observed in the performance of plants treated with compost based on different rates and time of application under different water stress regimes. Application before seed sowing and repeated application after seed sowing resulted in better plant performance compared to the application after seed sowing alone. Cowpea plants grown on soil amended with the higher rate (15t/ha) of compost both before and after seed sowing (C2B+C2A) also showed superiority in all the parameters considered. Cowpea dry matter yields were increased by 98, 110, 153 and 223 % in C1B+C1A, C1B+C2A, C2B+C1A and C2B+C2A compared with control (P<0.05). Chlorophyll content, carotenoid content, and stomata density of cowpea under water stress were also enhanced with compost application. Application of compost both before and after seed sowing enhanced cowpea growth and yield under water stress.